Faster eye movements in children with autism spectrum disorder. Issue 2 (26th December 2018) - Kovarski, Klara; Siwiaszczyk, Marine; Malvy, Joëlle; Batty, Magali; Latinus, Marianne
Abstract : Atypical visual exploration of both social and nonsocial scenes is often reported in Autism Spectrum Disorder (ASD) with less precise and longer saccades, potentially reflecting difficulties in oculomotor control. To assess a subset of oculomotor functions in ASD, 20 children with ASD and 21 age‐matched typically developing (TD) children (2.6–11.5 years) partook in three tasks of increasing complexity, while no explicit instruction was provided: a prosaccade gap task, a color and a "categorical" visual search tasks (a face among butterflies and vice‐versa). In addition to classical saccade metrics, we measured Distance error, (the distance between the target and the closest gaze position) and Time‐to‐target (the time taken to reach the target). In the prosaccade task, children with ASD were as accurate as TD children, yet faster to reach the stimulus. In the color visual search task, children with ASD were faster but less precise than TD children. In the categorical visual search, while TD children were more precise in orienting their gaze towards the face, children with ASD performed similarly in the two conditions; Time‐to‐target did not differ. Our results provide contradictory evidence regarding enhanced visual search ability in ASD: when considering response times, enhanced visual search performance was found in one task only, while when considering gaze precision no advantage was found. These three experiments demonstrate that the automatic saccadic system may function more rapidly in children with ASD. Nonetheless, a diminished sensitivity to bottom–up saliency and top–down influence might suppress this advantage in more complex visual environments. Autism Res 2019, 12: 212–224 © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay summary: Three experiments with no instructions were designed to assess oculomotor functions in children with Autism Spectrum Disorder (ASD). In a saccade task, children with ASD were faster than but as accurate as control children. In visual search tasks, accuracy and speed decreased with increasing complexity of visual environment. Children with ASD showed faster automatic visual orientation, but this might hinder exploratory behaviors, leading to difficulties in complex and social situations.